Communicating Environmental Science through Art: Scope, Applications, and Research Agenda - Chang, Michael (My University, 2015)
Traditionally science and art have been distinctly separate disciplines rarely practiced in concert, despite substantial evidence that art enhances understanding of science, technology, engineering and mathematics (STEM). Recently, art has been a means of communicating science, including environmental research. However, this movement of using art to communicate science has yet to be examined on a large scale. This study describes the key characteristics of the environmental science art movement by creating a database of 252 artworks and corresponding artists, coding for key data, and using a grounded theory approach to text analysis of artwork’s purpose statements. Results of the analysis show that environmental science art is a recent and increasingly prevalent phenomenon. Environmental science artists are gender balanced, reflect the age of environmental scientists and artists, and are trained in the arts 95% of the time and trained in the sciences 48% of the time. Catalogued science artworks date back four decades, with a majority of the artwork occurring since 2007. The artworks typically address issues of climate change, biodiversity, and highlight the connection between humans and the environment. Stated applications of the artworks include their artistic value, ability to increase awareness and educate, opportunity for interdisciplinary collaboration, ability for political commentary and activism, engagement and simulating experiences and connections to the environment, ability to foster dialogue towards a solution, and ability to be utilitarian. Overall, this study provides an overview of the scope and state of environmental science art, providing background and a foundation for future studies on how art could be used to communicate science and research about the environment.
Thesis (Master's)--University of Washington, 2015
Keywords: Environmental Science; Science Art; Science Communication; Science Education; Science Outreach; Environmental science; Communication; marine affairs